1999
DOI: 10.1111/j.1365-2621.1999.tb09870.x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Respiration of Apple Slices in Modified‐Atmosphere Packages

Abstract: Modified-atmosphere packaging was used to provide respiratory data for apple (Malus xdomestica Borkh.) slices at 0, 5, 10 and 15°C. The maximum rate of O 2 uptake increased with increasing temperature. The lowest O 2 partial pressure to which fruit could be exposed without fermentation also increased with increasing temperature. A mathematical model of film permeability data characterized the effect of fruit mass, film permeability to O 2 , activation energy of O 2 permeation, temperature, and the film type, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(84 citation statements)
references
References 14 publications
5
74
0
3
Order By: Relevance
“…Gorny [26] concluded that a reduction of O 2 levels to near 0 kPa retains firmness, extends shelf life, and is required to inhibit polyphenoloxidase (PPO) in many freshcut fruit products. Other studies reported significant changes in fresh-cut fruits after processing, in particular due to the effects of wounding caused by cutting, with a respiratory rate of about twice to three times higher than that reported for whole fruit [27,28].…”
Section: Figurementioning
confidence: 75%
“…Gorny [26] concluded that a reduction of O 2 levels to near 0 kPa retains firmness, extends shelf life, and is required to inhibit polyphenoloxidase (PPO) in many freshcut fruit products. Other studies reported significant changes in fresh-cut fruits after processing, in particular due to the effects of wounding caused by cutting, with a respiratory rate of about twice to three times higher than that reported for whole fruit [27,28].…”
Section: Figurementioning
confidence: 75%
“…The respiration rates during storage experiment was found to be least in 5°C, but relative percentage decrease was minimum in case of 12.5°C [14,[24][25][26], so there is less consumption of power and more economical to processor to store the minimally processed produce at relatively less energy waste.…”
Section: Resultsmentioning
confidence: 99%
“…Otra razón para su uso es su similitud con la respiración microbiana, para la que esta ecuación es muy utilizada. Lee et al, (1991), fueron los primeros en sugerir el uso de la ecuación de Michaelis-Menten para describir la tasa de respiración de los productos en función de la presión de O 2 y se ha utilizado para modelizar la tasa respiratoria de manzanas (Andrich et al, 1991;Andrich et al, 1998;Dadzie et al, 1996;Lee et al, 1991;Peppelenbos & Leven, 1996)), láminas de manzana (Lakakul et al, 1999), plátanos (Lee et al, 1991;Maneerat et al, 1997), arándanos Lee et al, 1996;Song et al, 1992), frambuesas , espárragos (Lee et al, 1991;Peppelenbos & Leven, 1996), bróculi (Lee et al, 1991;Peppelenbos & Leven, 1996), bróculi cortado (Haggar et al, 1992;Lee et al, 1991;Lee et al, 1996;Peppelenbos & Leven, 1996;Talasila et al, 1994), cerezas (Salvador et al, 2002), ensalada de col con zanahoria (McLaughlin & O'Beirne, 1999), lechuga cortada (Smyth et al, 1998), coliflor (Ratti et al, 1996) y otros muchos vegetales (Fonseca et al, 2002a). Este modelo respiratorio es válido sólo para respiración aeróbica, y la composición de los gases no se predice bien cuando la concentración de O 2 es muy baja.…”
Section: Métodos De Cuantificación De La Tasa Respiratoriaunclassified
“…Fonseca et al, 2002b, observaron que la col rizada hecha trizas/desmenuzada presentaba una tasa respiratoria aproximadamente el triple que la tasa respiratoria de las hojas enteras, como consecuencia tanto de la respuesta fisiológica a las heridas causadas por el corte, como del aumento de la superficie disponible para ejercer el intercambio gaseoso con el ambiente. De la misma forma, Lakakul et al, (1999), demostraron que láminas de manzana tenían una tasa respiratoria del orden de 2 ó 3 veces la TR de la fruta entera reportada (Gran, 1993;Kader et al, 1989), debido sobre todo a los efectos de las heridas y no tanto a la reducción de la resistencia de la difusividad producida por el laminado. El umbral de fermentación en las láminas de manzana estuvo alrededor de la mitad del reportado para las frutas enteras por Gran & Beaudry (1992), como consecuencia de la eliminación de la piel, cuya función es la de barrera del intercambio gaseoso, acoplado con una reducción en la longitud de la distancia de difusión.…”
Section: Pelado-cortadounclassified
See 1 more Smart Citation